Influence of Digital Language Movements on National Language Policy: Perspectives from Activists and Policymakers (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2026)
Digital language movements’ grassroots initiatives that use online platforms to advocate for linguistic recognition, orthographic standardization, and minority language visibility are increasingly shaping the landscape of national language policy. While scholarship in language planning has often emphasized state-driven processes, the influence of digitally mediated activism on policy design and implementation remains underexamined. This article investigates how such movements interact with national policy frameworks by analyzing perspectives from activists and policymakers. Drawing on campaign archives, policy documents, and semi-structured interviews, the study shows that digital initiatives operate through three main strategies: setting policy agendas via social media visibility, producing corpus resources such as lexicons and orthographies, and mobilizing pressure through transnational advocacy. Policymakers, however, perceive these initiatives ambivalently acknowledging their symbolic and cultural value while questioning their representativeness and practical feasibility. The findings highlight three key dynamics: digital activism is most effective in shaping early agenda-setting; activist-generated resources gain traction when validated by institutional allies; and structural policy adoption depends on bridging the digital divide and aligning with bureaucratic priorities. By foregrounding both tensions and collaborations between grassroots linguistic citizenship and institutional policy-making, the study advances understanding of how digital platforms reconfigure language planning in the twenty-first century and offers implications for more inclusive and sustainable policy design.
Keywords: Digital Activism; Language Policy; Language Planning; Linguistic Citizenship; National Policy